Sistem Penilaian Kinerja Karyawan PT Bank Syariah Indonesia Berbasis Website Menggunakan Algoritma Naive Bayes - Azmi Mutawalli, Khoirul; Muhajirin, Adi; Sari, Rafika (Jurnal Jaring SainTek, 2022)
This study focuses on developing an employee performance appraisal system that aims to evaluate employee performance at PT Bank Syariah Indonesia within the criteria set by the company aimed at classifying employee appraisals that can assist companies in classifying good or bad performance on the value of the employee. This method uses the nave Bayes classifier, a website-based employee performance appraisal system. The system will take the value of the criteria that have been set by the company such as: the value of neatness, loyalty, compliance, discipline, productivity and thoroughness. Based on the results of taking the value of these criteria, the system will issue an output that decides the classification of employees is classified as good or not good. Thus the system will determine whether the employee is good or bad.